2017
DOI: 10.1016/j.fpsl.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Shelf life extension of white mushrooms (Agaricus bisporus) by low temperatures conditioning, modified atmosphere, and nanocomposite packaging material

Abstract:  Shelf life extension of button mushrooms was evaluated by a combined approach  Temperature, packaging material, and modified atmosphere (MA) were investigated  Tissue softening is avoided for high CO 2 concentration (up to 20%)  The best performance was obtained for the 'nano' packaging with MA at 4°C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 34 publications
13
101
1
1
Order By: Relevance
“…However, CHSTiO2 mushrooms established that the nanocomposite material might decrease cell-wall-degrading enzyme activities, due to its high anti-oxidation capacities during the storage time [14]. Our results were linked with the finding of Gholami et al [2] who established that applying nanocomposite materials can enhance the firmness of mushroom samples. After 12 days of the storage period, the largest ∆E* values were established for the CHS (48.39), Figure 1e.…”
Section: Weight Loss Ratio and Texture Measurementssupporting
confidence: 71%
See 2 more Smart Citations
“…However, CHSTiO2 mushrooms established that the nanocomposite material might decrease cell-wall-degrading enzyme activities, due to its high anti-oxidation capacities during the storage time [14]. Our results were linked with the finding of Gholami et al [2] who established that applying nanocomposite materials can enhance the firmness of mushroom samples. After 12 days of the storage period, the largest ∆E* values were established for the CHS (48.39), Figure 1e.…”
Section: Weight Loss Ratio and Texture Measurementssupporting
confidence: 71%
“…Parameter L*, depending on the mushroom reflectivity surface that can show the luminosity [22]. Gholami et al [2] reported that the lower lightness values can be due to the coating films that can cause some changes on the mushroom surfaces.…”
Section: Color Attribute Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…To carry out the test, a probe of 5 mm diameter with a speed of 10 mm/min was used (Gholami et al, 2017). To carry out the test, a probe of 5 mm diameter with a speed of 10 mm/min was used (Gholami et al, 2017).…”
Section: D14 Zwick-roell) Equipped With a Load Cell (X Force Hp Nominalmentioning
confidence: 99%
“…Mushroom diameter increase has been studied over the years as part of mushrooms senescence (Guthrie, 1984). Some authors (Braaksma, Schaap, & Schipper, 1999; Gholami, Ahmadi, & Farris, 2017; Jiang, 2013) explained this behavior by a loss of cohesive forces that allows an intact position of the cap and veil. Other studies suggest that this expansion is related to the increasing behavior of the cells in the gill tissue (area beneath the cap) (Braaksma, van Doorn, Kieft, & van Aelst, 1998).…”
Section: Resultsmentioning
confidence: 99%